2012
DOI: 10.1177/0954407012442295
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate model for aerodynamic shape optimization of a tractor-trailer in crosswinds

Abstract: A surrogate model-based aerodynamic shape optimization method applied to the wind deflector of a tractor-trailer is presented in this paper. The aerodynamic drag coefficient of the tractor-trailer with and without the wind deflector subjected to crosswinds is analyzed. The numerical results show that the wind deflector can decrease drag coefficient. Four parameters are used to describe the wind deflector geometry: width, length, height, and angle. A 30-level design of experiments study using the optimal Latin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Non-gradient-based optimization of the surrogate model technique has been applied to not only crash optimization but also various practical examples. 2530 The technique is easy to use for the high-fidelity FE model of large-scale examples such as a full-scale vehicle FE model 4, 31 because it does not require sensitivity analysis. The responses of non-linear dynamic analysis are directly utilized to generate approximated mathematical functions of a surrogate model.…”
Section: Non-linear Dynamic Response Structural Optimization and The mentioning
confidence: 99%
“…Non-gradient-based optimization of the surrogate model technique has been applied to not only crash optimization but also various practical examples. 2530 The technique is easy to use for the high-fidelity FE model of large-scale examples such as a full-scale vehicle FE model 4, 31 because it does not require sensitivity analysis. The responses of non-linear dynamic analysis are directly utilized to generate approximated mathematical functions of a surrogate model.…”
Section: Non-linear Dynamic Response Structural Optimization and The mentioning
confidence: 99%
“…There are some studies in the literature that present models that are able to evaluate the forces and moments evolutions with the yaw angle. For instance, Gong et al [7] built a surrogate model based on the Kriging interpolation technique that finds the optimal wind deflector geometry in a tractor trailer to reduce drag in crosswind situations. Similarly, Ghoreyshi et al [8] developed a model that is able to predict the forces and moments changes with the Mach number, angle of attack, and side slip angle of an aircraft, and Zhang et al [9] presented a model to predict the derailment coefficient of a train in crossflows.…”
Section: Introductionmentioning
confidence: 99%
“…Using the sequential quadratic programming (SQP) method, the drag coefficient of the optimal design was reduced by 3.08% compared to the reference design and the relative error is only 0.84% compared to a CFD validation. Gong and Gu combined the kriging model and a multi-island genetic algorithm to optimize the shape of the wind deflector of a tractor-trailer [ 22 ]. Their results showed that the optimized shape of the wind deflector can decrease the drag of the tractor-trailer by 4.65%, compared to the original design.…”
Section: Introductionmentioning
confidence: 99%